Online Learning Innovation: Topic of “Natural and Energy Resources” Using Powtown-Based Learning Video - Upadana, I Putu Adi; Rati, Ni Wayan; Gading, I Ketut (Universitas Pendidikan Ganesha, 2021)
This research was conducted based on online learning during the pandemic. The use of learning media that is less innovative has an impact on students' interests and understanding. Therefore, it is necessary to develop innovative learning media that can increase students' interest and understanding. This study aims to describe the process of designing learning videos and to find out the results of the acceptance of learning videos on the content of science lessons for grade IV Elementary Schools to determine the acceptance of the products developed. The type of research used is development research, design on video development using the Powtoon application. The data collection method used is the subject questionnaire method in this study is the acceptability of the product which is assessed by 2 lecturers and 2 teachers. The instrument used to measure the acceptability of learning videos is a rating scale in the form of a learning video assessment sheet from an expert. The data obtained were then analyzed using the Gregory formula of 2x2 cross-tabulation to determine the acceptability of the developed learning video. The results of the analysis show that the value obtained from the four experts is 1.00 with a very high product acceptance qualification. Based on this analysis, it can be said that the learning videos developed are valid and can be used in the learning process in the fourth grade of elementary school.